Education for all: purpose and context - Haggis, Sheila M. (UNESCO ParisFR, 1991)
Identifies the basic learning needs which education must meet such at literacy, numeracy and problem-solving skills, as well as the knowledge, attitudes, and values needed by human beings to survive, and to function effectively in their societies. Explores the interplay between the education process and culture. Looks at the implications of new and broader concepts of literacy in designing strategies to reach adult learners. Examines the relationship between education and the 'world of work' and focusses on environmental education, population education and health education.